2020
DOI: 10.1111/jora.12572
|View full text |Cite
|
Sign up to set email alerts
|

Daily Links Between Helping Behaviors and Emotional Well‐Being During Late Adolescence

Abstract: We investigated daily associations between helping behaviors and emotional well‐being during late adolescence, examining whether these links depend on the recipient of help (i.e., friend vs. roommate), type of help (i.e., instrumental vs. emotional), and individual differences in the helper (i.e., gender and empathy). First‐year college students (N = 411, 63.5% women, Mage = 18.62 years) completed diary checklists for eight days, reporting whether they provided instrumental and emotional support to a friend or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 40 publications
1
16
0
Order By: Relevance
“…Shin et al (2011) found that the expression of positive affect predicted peer acceptance and greater initiation of positive interactions, and Agbaria (2020) showed that adolescents with a high level of satisfaction with life were more capable of establishing meaningful friendships, giving help, understanding and cooperating with other people, and resolving conflicts more efficiently. In particular, other studies have shown that high levels of positive affect and low levels of negative affect predict high levels of prosocial behaviour, although they also established that this relationship can be bidirectional (Armstrong-Carter et al, 2020;Chen et al, 2020).…”
mentioning
confidence: 99%
“…Shin et al (2011) found that the expression of positive affect predicted peer acceptance and greater initiation of positive interactions, and Agbaria (2020) showed that adolescents with a high level of satisfaction with life were more capable of establishing meaningful friendships, giving help, understanding and cooperating with other people, and resolving conflicts more efficiently. In particular, other studies have shown that high levels of positive affect and low levels of negative affect predict high levels of prosocial behaviour, although they also established that this relationship can be bidirectional (Armstrong-Carter et al, 2020;Chen et al, 2020).…”
mentioning
confidence: 99%
“…Supporting this idea, one study found that providing instrumental support to friends was not associated with positive emotions the same day (Morelli et al., 2015). Another study found that although providing instrumental support to friends was linked with positive emotions the same day, it also was simultaneously associated with negative emotions among young men (Armstrong‐Carter, Guassi Moreira, et al., 2020). Thus, helping friends with instrumental tasks might be linked to flatter diurnal slopes—a physical health risk factor— if it is experienced as stressful or taxing.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this interpretation is the theory of “skin deep resilience,” whereby youth can show positive adaptation on behavioral and emotional measures while simultaneously experiencing risk factors via markers of stress‐physiology that predict poor physical health and allostatic load (Hostinar & Miller, 2019). Providing instrumental support may be psychologically rewarding (Armstrong‐Carter, Guassi Moreira, et al., 2020), while simultaneously physiologically taxing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations